Spacelike and timelike pion electromagnetic form factor and Fock state components within the light-front dynamics - de Melo, JPBC; Frederico, T.; Pace, E.; Salme, G. (Amer Physical Soc, 2006)
The simultaneous investigation of the pion electromagnetic form factor in the space- and timelike regions within a light-front model allows one to address the issue of nonvalence components of the pion and photon wave functions. Our relativistic approach is based on a microscopic vector-meson-dominance model for the dressed vertex where a photon decays in a quark-antiquark pair, and on a simple parametrization for the emission or absorption of a pion by a quark. The results show an excellent agreement in the space like region up to -10 (GeV/c)(2), while in timelike region the model produces reasonable results up to 10 (GeV/c)(2).